Initial Validation of the Dutch Translation of the Caregiver Wish List: An Interview-Based Scale for Measuring Parenting Practices. (March 2018) - Thijssen, Jill; Broers, Nick J.; Muris, Peter; de Ruiter, Corine
Research has demonstrated that adequate parenting is an important determinant of a healthy social-emotional development in children. There is a need for valid assessment tools for measuring parenting quality, particularly in clinical settings. The Caregiver Wish List (CWL) is a new 53-item interview-based scale for assessing parenting practices. We examined the CWL's factor structure in a sample of 348 parents of children (4-11 years), 220 were drawn from the general population and 128 from a clinical setting. Exploratory factor analysis revealed five factors, which did not fully correspond with the hypothesized, original factor structure. Nonetheless, the extracted factors were meaningful and could be labeled as follows: adequate discipline, controlled responding, focus on positive behavior, consistency, and monitoring . All factors demonstrated adequate internal consistency. The factor structures in community and clinical samples were comparable, supporting the generalizability of the factor structure. Furthermore, the factors differentiated between community and clinical samples, with better parenting skills observed in the community sample. Finally, all factors were significantly and negatively related to child psychopathology, with stronger correlations for externalizing than for internalizing problems. Only 23 of the 53 original CWL items loaded on at least one of the five factors, indicating that the original CWL can probably be reduced in length without losing important content. Future research needs to examine if the extracted CWL factors are sensitive to change. The CWL's interview format provides opportunities for rapport building between parent and interviewer, and for reflection on parenting skills in terms of strengths and vulnerabilities.